Analyzing the Implementation of the Muhadharah Program for Developing Speaking Skills at the Ummu Sulaim Girls’ Islamic Boarding School - Nafisa Aulia Safannah; Muhammad Ripani Saputra (Program Studi Pendidikan Bahasa Arab Unisda Lamongan, 2026)
This study aims to analyze the implementation of the muhadharah program as an effort to develop the Arabic speaking skills (maharah kalam) of female students at Ummu Sulaim Girls' Islamic Boarding School. A qualitative case study approach was employed using observations, semi-structured interviews, and documentation as data collection techniques. The findings reveal that the implementation of the muhadharah program consists of three interconnected stages: planning, implementation, and evaluation. The program has contributed positively to improving students' self-confidence, vocabulary acquisition, and willingness to speak in public. Nevertheless, the findings indicate that the improvement of speaking competence has not yet reached an optimal level because the learning process remains predominantly oriented toward memorization-based speech delivery. Such an approach enables students to reproduce prepared texts accurately but provides limited opportunities to develop spontaneous oral communication, interactive language use, and communicative fluency, which are essential components of maharah kalam. Furthermore, the effectiveness of the program is influenced by several supporting factors, including a conducive Arabic-speaking environment, consistent scheduling, and guidance from supervisors. Conversely, limited vocabulary mastery, students' anxiety when speaking, and the lack of varied communicative teaching strategies constitute the primary obstacles to achieving better learning outcomes. These findings suggest that the effectiveness of the muhadharah program depends not only on the continuity of its implementation but also on the pedagogical approaches adopted during the learning process. Therefore, integrating communicative language teaching strategies, interactive speaking activities, and performance-based assessment is recommended to maximize students' speaking proficiency. This study contributes to the literature by providing an empirical analysis of the implementation of the muhadharah program in a female Islamic boarding school context and by identifying pedagogical aspects that require improvement to optimize the development of Arabic speaking skills. The findings may serve as a practical reference for Islamic boarding schools and Arabic language educators in designing more communicative and effective speaking development programs.